Callus Induction and Plant Regeneration from Mature Embryos of Glutinous Rice (Oryza sativa L.) Cultivar TDK1 - Souvanh Thadavong; Prapa Sripichitt; Wasana Wongyai; Peeranuch Jompuk (Agriculture and Natural Resources, 2002)
The present study was conducted to determine the optimum in vitro conditions for callus induction and plant regeneration from mature embryos (seeds) of glutinous rice cultivar TDK 1. It was revealed that embryos cultured on Murashige and Skoog (MS) agar medium supplemented with 2 mg/l 2,4-D and 500 mg/l L-proline under light condition produced the highest percentage of callus formation (96.91 %). The average size of callus produced was large (6.02 mm). The calli dehydrated by placing in petridishes with covers for 7 days under light condition before transferring onto regeneration medium generated higher frequency of shoot regeneration than the calli cultured on regeneration medium without dehydration. The most suitable medium for plant regeneration from dehydrated calli was MS agar medium supplemented with 1 mg/l IAA, 4 mg/l BA and 800 mg/l casein hydrolysate which induced the highest percentage of calli forming shoots (45.00 %) and each callus produced the largest number of shoots (average 15 shoots). The shoots were rooted at the highest rate (100 %) when transferred onto MS agar medium supplemented with 1 mg/l NAA. The complete plantlets were thereafter transplanted to grow under greenhouse condition. They were morphologically normal and fertile.